Solutions or Alternatives to Protect Livestock, Especially Buffalo from the Risk of Drought in Basra Governorate - Tabeekh, Mudhar A. S. Abu; Maktoof, Ali Rasheed; Mohsen, Hamed Abdul Majid Abdul (Canadian Journal of Agriculture and Crops, 2017)
Buffaloes in Iraq represent the most productive animal since its domestication in Mesopotamia about prehistoric era. Domestic water buffaloes are common in the marshes of southern Iraq. On Sunday the UN cultural agency, UNESCO, added the marshlands and the ancient Sumerian cities that once flourished among them to its list of sites. During the period of 1991 -2003, southern Iraqi marshes were ditched and drained by the previous Iraqi regime for political reasons. The destruction and drainage of the Iraqi marshes affect the wildlife of southern Iraq. The marshes today remain one of the poorest areas. The goals of this research were to provide needed information regarding the status of buffalo following reflooding of the Mesopotamian marshlands, as well as contribute solutions or alternatives to protect buffalo from the risk of drought.